Operationalizing the Right to Information Act through E-Governance in Bangladesh: Challenges and Opportunities. Issue 8 (11th June 2021) - Baroi, Harold Sougato; Alam, Shawkat
ABSTRACT: Over the years, lack of transparency and accountability has become a common feature in the delivery of public services in Bangladesh. Bangladesh's introduction of The Right to Information Act 2009 ('RTI') was intended to achieve greater access to government information and to promote better public transparency and accountability. However, this article suggests that there has been minimal improvement in the situation despite recent legislative changes. The implementation strategies, which follow a top-down approach, is inappropriate and ineffective in promoting the involvement of citizens, which is particularly important in RTI related practices. The article proposes that the present challenges in encouraging people to get involved in the RTI process can be addressed appropriately with an Integrated E-governance Model, and that the proposed approach could be an alternative to the present model for the implementation of the RTI Act in Bangladesh.